Gangrenous cholecystitis due to rare actinomyces odontolyticus infection in patient with pancreatic adenocarcinoma: A case report - Chadi Nahal; Phillip Blotevogel; Vidyaratna A. Fleetwood (IDCases)
Introduction: Gangrenous cholecystitis is a life-threatening complication of acute cholecystitis. Although typically associated with Bacteroides infection, immunocompromised patients, such as those receiving chemotherapy, are more susceptible infection with uncommon organisms. To our knowledge, there are no previously reported cases of gangrenous cholecystitis secondary to actinomyces odontolyticus, which we present here. Case: A 48 year-old male with risk factors for cholecystitis including male sex, ERCP with stent placement, and immunocompromised state secondary to chemotherapy for pancreatic adenocarcinoma presented with worsening abdominal pain and altered mental status. Over the prior 2 months, he had recurrent episodes of abdominal attributed to the pancreatic cancer. Laboratory values were remarkable for leukocytosis and elevated alkaline phosphatase and lactic acid. He was administered antibiotic therapy with piperacillin-tazobactam and urgently underwent a sub-total open cholecystectomy. Intra-abdominal fluid cultures grew actinomyces odontolyticus. In addition to piperacillin-tazobactam, he was subsequently administer vancomycin for clostridium difficile infection and micafungin. De-escalating antibiotics resulted in worsening leukocytosis. Per his previously expressed wishes in the setting of pancreatic cancer, he was discharged to home hospice and expired afterwards. Discussion: This is the first reported case of gangrenous cholecystitis secondary to infection with actinomyces odontolyticus. The patient’s immunosuppressed state made him susceptible to rare organisms and likely delayed the appearance of symptoms, which are also similar to the symptoms of pancreatic cancer causing biliary obstruction. Cholecystitis should be included in the differential diagnosis of epigastric pain for immunocompromised patient with pancreatic cancer and history of ERCP.